Outsourcing malaysia federal tax audit: The stakeholders' views - Ahmad N.; Mohammed Z.M.; Iskandar T.M.; Faizal S.M.; Mustafa Mohd Hanefah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus